Arbuscular Mycorrhizal Fungi Increase Pb Uptake of Colonized and Non-Colonized Medicago truncatula Root and Deliver Extra Pb to Colonized Root Segment - Haoqiang Zhang; Wei Ren; Yaru Zheng; Yanpeng Li; Manzhe Zhu; Ming Tang (Microorganisms, 2021)
Arbuscular mycorrhizal (AM) fungi establish symbiosis and improve the lead (Pb) tolerance of host plants. The AM plants accumulate more Pb in roots than their non-mycorrhizal counterparts. However, the direct and long-term impact of AM fungi on plant Pb uptake has been rarely reported. In this study, AM fungus (Rhizophagus irregularis) colonized and non-colonized roots of Medicago truncatula were separated by a split-root system, and their differences in responding to Pb application were compared. The shoot biomass accumulation and transpiration were increased after R. irregularis inoculation, whereas the biomass of both colonized and non-colonized roots was decreased. Lead application in the non-colonized root compartment increased the R. irregularis colonization rate and up-regulated the relative expressions of MtPT4 and MtBCP1 in the colonized root compartments. Rhizophagus irregularis inoculation increased Pb uptake in both colonized and non-colonized roots, and R. irregularis transferred Pb to the colonized root segment. The Pb transferred through the colonized root segment had low mobility and might be sequestrated and compartmented in the root by R. irregularis. The Pb uptake of roots might follow water flow, which is facilitated by MtPIP2. The quantification of Pb transfer via the mycorrhizal pathway and the involvement of MtPIP2 deserve further study.